2010
DOI: 10.1007/s11553-010-0234-5
|View full text |Cite
|
Sign up to set email alerts
|

Die Uni ist kein Ponyhof

Abstract: SchwerpunktViele akademisch ausgebildete Menschen empfinden im Rückblick -oft ein wenig verklärt -die Studienzeit als die schönste Zeit in ihrem Leben. Auch in der öffentlichen Wahrnehmung überwiegt oft (immer noch) der Eindruck, Studierende führten ein unglaublich privilegiertes Leben, sie könnten sich entsprechend ihrer individuellen Interessen entfalten, lebten sich sexuell ungezügelt aus und hätten freie Zeit und Müßig-gang in Hülle und Fülle. Keine Frage, ein Studium bietet sicher eine Menge Freiheiten. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Recent surveys conducted among German university students (e.g., TK-Forsa-Survey, 2012) have revealed that one out of five students provide affirmative responses to questions that assess depressive symptoms and depression severity. Although first-year freshmen are particularly vulnerable to stress and stress-induced depressive and anxiety symptoms (e.g., Ackermann and Schumann, 2010;Farrer et al, 2016), stressors are highly prevalent among all groups of students because they continuously experience stress that is caused by regular examinations, fixed deadlines, and the constant need to perform well to increase their likelihood of later academic achievement. Several studies already found positive correlations between stress and illness in university students on the one hand and between perceived stress, anxiety and depression on the other hand (e.g., Tosevski et al, 2010;Farrer et al, 2016).…”
Section: Mental Health and Well-being Among University Studentsmentioning
confidence: 99%
“…Recent surveys conducted among German university students (e.g., TK-Forsa-Survey, 2012) have revealed that one out of five students provide affirmative responses to questions that assess depressive symptoms and depression severity. Although first-year freshmen are particularly vulnerable to stress and stress-induced depressive and anxiety symptoms (e.g., Ackermann and Schumann, 2010;Farrer et al, 2016), stressors are highly prevalent among all groups of students because they continuously experience stress that is caused by regular examinations, fixed deadlines, and the constant need to perform well to increase their likelihood of later academic achievement. Several studies already found positive correlations between stress and illness in university students on the one hand and between perceived stress, anxiety and depression on the other hand (e.g., Tosevski et al, 2010;Farrer et al, 2016).…”
Section: Mental Health and Well-being Among University Studentsmentioning
confidence: 99%
“…The mental health of students Psychosocial problems, exhaustion, psychosomatic complaints or fears resulting in sleep disorders, nervousness, concentration problems or mood swings are prevalent among German students [11]. Students showed increased alcohol consumption [12].…”
Section: Effects Of Study-related Stress On the Course Of Studymentioning
confidence: 99%
“…First, new role conflicts caused by breaking away from family and friends and the associated independence are suspected to be a crisis-prone biographical phase between adolescence and adulthood [11], which appears to be particularly significant for international students. Overcoming this causes orientation difficulties in the formation of one's own identity [11]. In addition, role conflicts also arise, where students try to perform several social roles at the same time.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy often fosters the prioritizing of achievement and output over well-being and health. The focus on students’ health is more recent and has been fueled by the health concerns caused by the European Bologna reform process and the implication it has on students ( 2 , 3 ). Furthermore, students are in a special stage of their lives.…”
Section: Introductionmentioning
confidence: 99%